Fl-160. A surface antigen of Trypanosoma cruzi that mimics mammalian nervous tissue (The Rockefeller University Press, 1989)
Chagas' disease, caused by Trypanosoma cruzi, is an excellent model for autoimmune disease induced by an infectious agent. Transfer of T cells, directed against crossreactive antigens of T. cruzi and nervous tissue, have been shown to reproduce pathology found in chronic Chagas' disease. We used recombinant DNA technology to characterize one of these crossreactive antigens (Fl-160). We have cloned DNA from T. cruzi, which expresses a protein corresponding to a 160-kD protein found on the surface of the trypanosome, overlying the flagellum. This clone hybridizes to a 4.5-kb poly(A)+ RNA that is distributed in a differentiation-specific manner, suggesting expression of this protein is transcriptionally controlled. Antibodies to this protein crossreact with a 48-kD mammalian nervous tissue protein found in sciatic nerve, brain, and myenteric plexi of gut. The myenteric plexi are destroyed by inflammatory infiltrates in Chagas' disease, leading to the characteristic megaesophagus and megacolon Chagas' disease pathology. Thus, this antigen is a candidate antigen for autoimmune mimicry leading to nervous tissue pathology.